2022
DOI: 10.1002/jso.27024
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term experience with intraoperative electron radiation therapy boost in extremity sarcoma

Abstract: Background In patients with extremity soft tissue sarcoma (eSTS), we describe outcomes of preoperative external beam radiation therapy (EBRT), limb‐sparing surgery (LSS), and intraoperative electron radiation therapy (IOERT). Methods One hundred and eighteen patients with eSTS treated between October 17, 2002 and July 28, 2021 were identified. EBRT was delivered preoperatively followed by LSS and IOERT. Results The median follow‐up was 24.9 months. The presentation was primary in 102 (94%) patients and recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…For early-stage STS, surgery is often the preferred primary treatment. However, for advanced or locally advanced cases, previous studies have proposed that surgery may be combined with radiation or chemotherapy to optimize therapeutic outcomes compared to surgery alone, such as mastectomy ( 37 , 38 ). Chemotherapy plays a crucial role in STS treatment, employing pharmaceutical intervention to disrupt cancer cell growth and division.…”
Section: Discussionmentioning
confidence: 99%
“…For early-stage STS, surgery is often the preferred primary treatment. However, for advanced or locally advanced cases, previous studies have proposed that surgery may be combined with radiation or chemotherapy to optimize therapeutic outcomes compared to surgery alone, such as mastectomy ( 37 , 38 ). Chemotherapy plays a crucial role in STS treatment, employing pharmaceutical intervention to disrupt cancer cell growth and division.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported good local control and overall survival outcomes, indicating the potential effectiveness of this treatment strategy. Laughlin et al reviewed their long-term experience with an intraoperative electron radiation therapy boost in extremity sarcoma treatment and demonstrated favorable local control rates and overall survival with low rates of toxicity 52 . Finally, Wang et al evaluated the clinical outcomes of patients with localized soft-tissue sarcoma treated with neoadjuvant chemoradiotherapy or radiation therapy 53 .…”
Section: Radiation Therapymentioning
confidence: 99%